2006
DOI: 10.1073/pnas.0601058103
|View full text |Cite
|
Sign up to set email alerts
|

Distinct structural and mechanical properties of the nuclear lamina in Hutchinson–Gilford progeria syndrome

Abstract: The nuclear lamina is a network of structural filaments, the A and B type lamins, located at the nuclear envelope and throughout the nucleus. Lamin filaments provide the nucleus with mechanical stability and support many basic activities, including gene regulation. Mutations in LMNA, the gene encoding A type lamins, cause numerous human diseases, including the segmental premature aging disease Hutchinson-Gilford progeria syndrome (HGPS). Here we show that structural and mechanical properties of the lamina are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
372
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 341 publications
(403 citation statements)
references
References 34 publications
26
372
2
3
Order By: Relevance
“…25,26 Based on this milderthan-expected disruption of binding, and the weak binding of lamin C and ∆90 tails we suggest the Ig-fold may be stabilized by interactions with another region of the tail, specifically residues 564-608 in AB-2. Inefficient actin binding and bundling by the lamin A ∆50 protein ('progerin') might contribute to the structural collapse of the lamina network in HGPS patient nuclei 12 and might also impair dynamic rearrangements of nuclear actin polymers in response to mechanical stress. 12,47 Based on these findings, we propose that prelamin A residues 647-664, which are normally cleaved, carboxymethylated, farnesylated and then proteolytically removed during lamin A maturation in vivo, might act in concert with residues 385-393 52 to auto-inhibit prelamin A binding to actin and potentially other partners that bind the Ig-fold region, 27 including nuclear titin, 19 Sun1, 48 Sun2, 49 emerin 15 and nesprins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 Based on this milderthan-expected disruption of binding, and the weak binding of lamin C and ∆90 tails we suggest the Ig-fold may be stabilized by interactions with another region of the tail, specifically residues 564-608 in AB-2. Inefficient actin binding and bundling by the lamin A ∆50 protein ('progerin') might contribute to the structural collapse of the lamina network in HGPS patient nuclei 12 and might also impair dynamic rearrangements of nuclear actin polymers in response to mechanical stress. 12,47 Based on these findings, we propose that prelamin A residues 647-664, which are normally cleaved, carboxymethylated, farnesylated and then proteolytically removed during lamin A maturation in vivo, might act in concert with residues 385-393 52 to auto-inhibit prelamin A binding to actin and potentially other partners that bind the Ig-fold region, 27 including nuclear titin, 19 Sun1, 48 Sun2, 49 emerin 15 and nesprins.…”
Section: Resultsmentioning
confidence: 99%
“…Inefficient actin binding and bundling by the lamin A ∆50 protein ('progerin') might contribute to the structural collapse of the lamina network in HGPS patient nuclei 12 and might also impair dynamic rearrangements of nuclear actin polymers in response to mechanical stress. 12,47 Based on these findings, we propose that prelamin A residues 647-664, which are normally cleaved, carboxymethylated, farnesylated and then proteolytically removed during lamin A maturation in vivo, might act in concert with residues 385-393 52 to auto-inhibit prelamin A binding to actin and potentially other partners that bind the Ig-fold region, 27 including nuclear titin, 19 Sun1, 48 Sun2, 49 emerin 15 and nesprins. 50,51 We hypothesize that lamin head-to-tail polymerization, proposed to involve lamin A residues 385-393, 52 is also subject to auto-inhibition in prelamin A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies showed that LA⌬50/progerin is less soluble than WT-LA (22), the solubility of E145K-LA was also tested. Sequential extraction of FLAG-E145K-LA and FLAG-WT-LA expressing HeLa cells, however, showed no differences in the solubilities of WT-LA and E145K-LA, suggesting that both assembled into stable structures under these conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, progerin has been shown to affect the mechanical stability of the nucleus (58), and a recent study has indicated that progerin interferes with lamin A and lamin B1 homopolymer formation and results in the production of structurally abnormal progerin-containing heteropolymers (50). In the future, it will be important to define the extent to which these abnormalities are affected by an FTI.…”
Section: In the Zmpste24mentioning
confidence: 99%